Relasi Guru-Murid dalam Pendidikan Humanis-Transendental: Studi Komparatif Gagasan KH. Hasyim Asy’ari dan Carl Rogers - Wafi, Abdul; Ali Mudlofir; Afrian Ulu Millah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
Modern education faces a multidimensional crisis, marked by the reduction of its meaning to mere knowledge transfer and a decline in students’ moral values. Contemporary pedagogical approaches tend to emphasize cognitive aspects while neglecting the ethical, emotional, and spiritual dimensions essential to humanizing education. This study aims to examine and compare the teacher-student relational concepts of Carl Rogers and KH. Hasyim Asy’ari, to offer an integrative alternative approach: the humanistic-transcendental model. Employing a qualitative method through library research, this study analyzes two primary sources—Freedom to Learn by Carl Rogers and Adab al-‘Alim wa al-Muta‘allim by KH. Hasyim Asy’ari—alongside relevant secondary literature, using content and comparative analysis. The findings reveal that Rogers emphasizes learning freedom, empathy, and dialogical relationships through the principles of unconditional positive regard and congruence. Meanwhile, Hasyim Asy’ari highlights adab (ethical conduct), exemplary character, and deep spiritual relationships. Both agree that the teacher-student relationship must be ethical, relational, and transformative. The implications of this study reinforce the urgency of integrating humanistic and spiritual values into Indonesian educational praxis, particularly in the context of the Merdeka Curriculum.